2018
DOI: 10.29313/mediator.v11i2.3947
|View full text |Cite
|
Sign up to set email alerts
|

Framing Analysis of News Article about Clashes between Police and Terrorist Prisoners in Indonesia Publishing by ABC.net.au and SBS.com

Abstract: In 10 May 2018, six policemen had been killed in clashes between Indonesian police and prisoners in the jail in the Mobile Police Brigade (Brimob) headquarters in Depok, West Java. It was located in outskirts of Jakarta. The incident had attracted people’s attention from all around the world. One of the reasons was because it taken place in the headquarters of the police. It can be said as a dramatic tragedy. Another reason that it magnetized public’s awareness was because it involved so call terrorist prisone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…State news agency content is being influenced by government policy, so that the coverage will support the government's interest (Du & Li, 2017;Primayanti, 2015;Rantanen et al, 2019;Watanabe, 2017;Zhang & Boukes, 2019). In terrorism, the state news agency will never cover the news or statement from the group/person whose claiming responsibility for the terrorism act (Junaedi, 2017), it makes the objectivity become the rare things in terrorism news (Sukarno, 2011) The target audiences also influences the state news agency news frame (Satriani, 2018). In order to know the general view about the audiences of both state news agencies, the authors use a literature review about the social-political condition in NZ and Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…State news agency content is being influenced by government policy, so that the coverage will support the government's interest (Du & Li, 2017;Primayanti, 2015;Rantanen et al, 2019;Watanabe, 2017;Zhang & Boukes, 2019). In terrorism, the state news agency will never cover the news or statement from the group/person whose claiming responsibility for the terrorism act (Junaedi, 2017), it makes the objectivity become the rare things in terrorism news (Sukarno, 2011) The target audiences also influences the state news agency news frame (Satriani, 2018). In order to know the general view about the audiences of both state news agencies, the authors use a literature review about the social-political condition in NZ and Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
“…Although the SBS media is also owned by the Australian government, they have a different audience target from ABC. This makes SBS news is more straightforward than ABC Satriani (2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Hall in Eriyanto (ibid), "the work process of creating and producing news is not something neutral, but there is an ideological bias practised by journalists consciously or not." Sobur believes that framing analysis is used to examine how media's ideology constructs the facts (Satriani, 2018). Pan and Kosicki in Satriani (ibid) define framing analysis as an approach that is used to analyse news discourse, especially dealing with the creation and bargain of the public discourse related to public policy issues.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, if the word chosen has a negative connotation, then the news is unfavorable. The research carried out by Satriani (2018) showed how sbs.com's news has a slight bias through the choice of the word 'Islamic militarism' to refer to the perpetrators of crimes in the incident of clashes between the Indonesian police and detainees at the Brimob Kelapa Dua prison, Depok (Satriani, 2018). Online media abc.com.au and sbs.com show different news frames, abc.com.…”
Section: Rhetorical Structurementioning
confidence: 99%